Influence of Various Types of Twisted Tape inserts on Hydrody-namic, Pressure Drop and Thermal Heat Performance in Heat Ex-changers: A Review Study - Al-Obaidi, Ahmed Ramadhan; Jaffal, Hayder Mohammad (Anbar Journal of Engineering Sciences, 2021)
Numerous inserts types are employed in different heat transfer improvement application devices. In this review study is forced on various types of twisted tape inserts in heat exchanger pipe. Geometrical configurations of twisted tape for example twist direction; length, width, space, twist ratio etc. were highly effect on flow pattern, hydrodynamic flow and heat transfer performance. In this review study observed that using different types of twisted tapes can improve thermal performance and hydrodynamic as compared to smooth pipe (without twisted tape). The review investigations found that improvement of thermal performance happens owing to decrease in pipe cross area, leads to rise in mixing flow, turbulence flow intensity flow and rise in swirl flow established through different kinds of twisted tapes. This article dealt with investigations pub-lished in corrugated pipes with varying field applications to provide good information for engi-neers and designers whom dealing and concerning with improvement of heat performance in heat exchanger corrugated pipes.